Examination of the Relationship Among Balance, Physical Activity, and Anthropometry in Athletes With Visual Impairments. (January 2022) - Esatbeyoglu, Ferhat; Kin-İsler, Ayse; Peyré-Tartaruga, Leonardo A.
Introduction: Although it is well documented in the literature that individuals with visual impairments have low physical activity levels and impaired body compositions and postural controls compared with peers without vision loss, the relation between these parameters in athletes with visual impairments is unknown. Research Question: Here, we (i) evaluated the physical activity levels, balance measures, and anthropometry parameters in athletes with visual impairments and peers without vision loss controls and (ii) compared these variables between the two groups. Methods: We designed a retrospective observational study with parallel groups conducted on 33 athletes with visual impairments and 33 sighted controls matched for age and sex. We also utilized a questionnaire about physical activity levels and assessed static balance for 4 conditions (eyes-open firm surface, eyes-closed firm surface, eyes-open foam surface, and eyes-closed foam surface) and anthropometry. Results: In athletes with visual impairments, body composition, body mass index (BMI), physical activity level, and static balance parameters revealed no significant relationship ( p > .05), whereas eyes-open and -closed firm and foam surface conditions were positively related with physical activity at a moderate level ( r = 0.39, r = 0.38, p < .05, respectively). Moderate-intensity and high-intensity physical activity was positively associated with fat-free mass ( r = 0.82, r = 0.68, p < .01, respectively) and negatively related with body mass, fat %, and fat mass ( r = −0.67, r = −0.52, r = −0.72, r = −0.66, r = −0.50, r = −0.50, p < .01, respectively). Athletes with visual impairments presented lower static balance than the sighted controls for three conditions, while eyes-closed foam surface scores were similar in both groups. The physical activity levels were higher for athletes with visual impairments ( p < .05). However, we found no difference in the body composition and BMI between two groups ( p > .05). Discussion: Sports participation from individuals with visual impairments is related to higher physical activity levels, resulting in better anthropometric profile. The balance control was not related to physical activity levels in athletes with visual impairments.